Novel Validated UV Spectroscopic Method for Routine Analysis of Decitabine Drug Substance - Awasthi, Ankit; HM, Dheeraj; Sathyanarayana, Muddukrishna Badamane (Indian Journal of Pharmaceutical Education and Research, 2020)
Objectives: In the proposed study, a basic, novel, protected economic, delicate and cost-effective UV-Spectrophotometric technique for the analysis of Decitabine which is antineoplastic drug. Methods: The created method was approved according to ICH rules. The decitabine indicated maximum absorption at 221 nm. This strategy can successfully apply for estimation of Decitabine in active pharmaceutical ingredient (API) form for routine examination with UV identification at 221 nm. A Shimadzu UV-Visible spectrophotometer 1800 with 1 cm quartz cells and Acetonitrile (ACN) as diluent was utilized in this technique. Results: The Developed technique obeyed Beer's-Lambert's law in the conc. of 5.0-15.0 ug/ml, having R2 of 0.9993 and 99.82%±0.75 recovery of decitabine was found. Different approval parameters like linearity, accuracy, precision and robustness were performed and were found to be within the limits as per the guidelines of ICH.
Keywords: Decitabine; UV-spectroscopy; Validated method; ICH guidelines; Beer’s; Lambert’s law; Analysis